Significance of expression of estrogenic receptors alpha and beta during the course of various types of skin ageing - Zegarska, Barbara; Jóźwicki, Wojciech; Zegarski, Wojciech; Czajkowski, Rafał; Pokrywczyńska, Marta (Menopause Review/Przegląd Menopauzalny, 2011)
Background: Skin ageing is a complicated process of various biological, biochemical and molecular mechanisms. It seems that a significant role in the ageing process in women is played by lack of stimulation of oestrogenic receptors (ER). Aim of the study : To assess differences in the degree of expression of ER and ER receptors in the epidermis and in the corium during the course of various types of skin ageing. Material and methods: The study included a group of 60 healthy women with various symptoms of skin ageing, from 26 to 62 years old. Three independent groups were distinguished; each group contained 20 persons. Group I consisted of women with symptoms of menopausal skin ageing, group II comprised women with symptoms of photoageing, and group III included women with symptoms of chronological ageing. Biopsy specimens were taken in all women from the pre-auricular region for immunohistochemical examinations. Measurements concerning expression of ER and ER1 receptors were performed using monoclonal mouse antibodies against human receptor  (Monoclonal Mouse Anti-Human Estrogen Receptor , clone 1D5, of IgG1 kappa isotype) and 1 (Monoclonal Mouse Anti-Human Estrogen Receptor 1, clone PPG5/10), respectively. Results : ER expression was not observed in the majority of studied women in all groups both in the epidermis and in the corium, and even if expression was found, its intensity and extent were small. ER1 expression occurred in all analysed women both in the epidermis and in the corium with various intensity and extent, but was the strongest in group I. Conclusions: 1. There are no statistically significant differences in intensity and extent of ER expression in groups of chronological and menopausal ageing and photoageing women. 2. There is significantly higher intensity and extent of ER1 expression during menopausal ageing.